Relationships of Fungicide Application to Late-Blight Development and Potato Growth Parameters in the Tropical Highlands of Uganda and Kenya - Olanya, O. M.; El-Bedewy, R.; Ojiambo, P. S.; Hakiza, J. J. (International Potato Center, 2001)
The impact of fungicide applications on late blight development, potato growth parameters, and yield was quantified at field sites in Kenya and Uganda during the 1999 and 2000 cropping seasons. In Kenya, three potato varieties were evaluated at two sites, at altitudes of 1800 m and 2200 m. In Uganda, three varieties were evaluated at one site at an altitude of 2400 m. Leaf, stem, root, and tuber biomass were sampled and quantified during the cropping season. Dithane M-45 fungicide was applied to the experimental plots at the onset of disease at intervals of 7, 14, and 21 days. Final tuber yields differed significantly by as much as 15% between fungicide-treated and untreated controls across the three sites. The severity of late blight differed among sites and between years as a result of variations in environmental conditions. Fungicide application intervals significantly affected disease progress, and the area under disease progress curve (AUDPC) was significantly lower in the fungicide-treated plots than in the control (unsprayed) plots. Tuber biomass accumulation was also significantly affected by fungicide applications. Varieties Tigoni and Rutuku have relatively higher levels of polygenic resistance to late blight and showed low levels of disease severity
Keywords: Tropical Highlands; Fungicide Application; Late-Blight Development